Use of free microvascular flaps in the management of the head and neck defects - Nikolić Živorad; Jeremić Jelena; Milosavljević Radoje (Vojnosanitetski Pregled)
Background/aim: In the field of contemporary head and neck reconstructive surgery, free vascularized tissue transfer is becoming a gold standard. The aim of this study was to review our clinical results and experience, with use of free microvascular flaps and compare them with the recently published patient series. Methods. During the period from 2001 to 2005, 37 patients underwent microsurgical reconstruction after the tumor ablation in the region of head and neck. Flap viability was monitored intraoperatively with the Ackland test and postoperatively by the clinical observation and mini-Doppler test. Results. The overall success rate was 83.8%. The complications that appeared were: one complete flap necrosis due to venous thrombosis, and five late flap ischemic necroses, in the period from the 10th to 14th postoperative day. Conclusion. Free flap reconstruction of the head and neck is a surgical technique that provides the reconstruction of complex and extensive defects, that could not be performed by using local or regional flaps.